Bridging the gap: uniting a divided urban core through riverfront design in Topeka, Kansas - Johnson, Jacob Boyd (Kansas State University, 2019)
Civilization has been defined by rivers. Initially people settled by rivers for sustenance. Later, rivers connected societies and were used for transportation. Rivers were both vital and fatal to those exploring new lands. Rivers were used to bridge our continent and to unite the eastern and western portions of the United States in the 1800’s. Once glorified by explorers such as Lewis and Clark, the changes in transportation and technology in the last 200 years have caused us to take rivers for granted. As a result, American cities have neglected their rivers, disconnected from them, and forgotten them. Rivers physically divide many cities causing urban areas to lose cohesiveness, history, and culture rooted in their rivers. Urban rivers have flood walls, levees, railroads, streets, and many other barriers hindering connection to their waters. Reconnecting with rivers can transform the core fabric and identity of cities. “Riverfronts have the power of connecting urban dwellers to the natural processes, which are generally hidden in the urban context, to the history of the city, and to other city dwellers of different classes or backgrounds” (May 2006). The goal of this research is to create a connected and transitional riverfront corridor for the City of Topeka, Kansas by connecting the central and the north sides of town via a linear park bridge. The focus of the research is to create a masterplan for the Kansas riverfront to reconnect the people of Topeka, Kansas to the river that runs through their city. The target area will be inventoried, analyzed, and designed to create a riverfront design that creates an identity for people of Topeka and reconnects the city back to its river. This project will also create a riverfront destination which includes the Kansas river as part of a unified urban core for the city of Topeka. The multi-use bridge will become a focal point and a destination in itself. This project hopes to “establish a reason for people to return to the water’s edge showing them potential uses in a very personal way” (Torre 1989). This riverfront project will not only connect north and central Topeka, but it will connect residents and visitors Topeka to the river itself.
Keywords: Connection; Linkage; Barriers; Riverfront Design; Topeka, Kansas; Urban Core